1997
DOI: 10.1021/ie960431j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mercuric Nitrate on Species and Reactions Related to Chlorine Dioxide Formation

Abstract: Mercuric ions influence reactions and intermediates that are involved in forming chlorine dioxide from chlorate ions. Addition of mercuric ions to reaction solutions can aid in understanding the mechanism and kinetics of this system. Mercuric ions do not react with aqueous solutions of chlorine dioxide unless those solutions contain chlorous acid. This unusual effect has enabled us to confirm that chlorous acid is an intermediate in the formation of chlorine dioxide in the methanol−chlorate reaction. This work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…17 As an exception, the disappearance of ClO 2 was found in acidic aqueous solution of chlorite ion, chlorine dioxide, and mercury(II). 18 This phenomenon was used to confirm the formation of chlorous acid as an intermediate in the oxidation of methanol with chlorate ion. On the basis of the chemical properties of oxychlorine species and Hg(II), the decay of ClO 2 is quite an unexpected phenomenon and indicates very unique features of the Hg(II)-ClO 2 --ClO 2 system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 As an exception, the disappearance of ClO 2 was found in acidic aqueous solution of chlorite ion, chlorine dioxide, and mercury(II). 18 This phenomenon was used to confirm the formation of chlorous acid as an intermediate in the oxidation of methanol with chlorate ion. On the basis of the chemical properties of oxychlorine species and Hg(II), the decay of ClO 2 is quite an unexpected phenomenon and indicates very unique features of the Hg(II)-ClO 2 --ClO 2 system.…”
Section: Introductionmentioning
confidence: 99%
“…Redox reactions of chlorite ion are often coupled with catalytic decomposition of this species producing chlorine dioxide which is stable under acidic condition . As an exception, the disappearance of ClO 2 was found in acidic aqueous solution of chlorite ion, chlorine dioxide, and mercury(II) . This phenomenon was used to confirm the formation of chlorous acid as an intermediate in the oxidation of methanol with chlorate ion.…”
Section: Introductionmentioning
confidence: 99%
“…Burke et al (1993) measured the rate in the absence of chloride. They correlated all of the experimental data in terms of an empirical expression, RCIO, = 1.5 X 10'" Effect of mercuric salts Indu et al (1997) used mercuric ion as a diagnostic tool in studies of chlorine dioxide formation. Mercuric ions: (1) remove chloride from solution by forming soluble HgCI,; (2) rapidly decompose chlorite ions in solution; and (3) do not react with chlorine dioxide in solution, unless chlorite ions are present.…”
Section: Introductionmentioning
confidence: 99%
“…No change in chlorine dioxide concentration indicates that chlorite is not present, or is present in very low concentration. Indu et al (1997) referred to the work of Gordon and Emmenegger (1966) who suggested that chlorite and chlorinc dioxide form a complex in solution c10, + c10; --3 Cl20, (18) Indu et al speculated that mercuric decomposes chlorine dioxide in this complex form.…”
Section: Introductionmentioning
confidence: 99%